2020
DOI: 10.1007/s10792-020-01412-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the clinical characteristics and copy numbers of DNA of cytomegalovirus determined by real-time PCR

Abstract: Purpose To determine whether there is a correlation between the clinicals characteristics including various types of keratic precipitates and the copy numbers of the DNA of cytomegalovirus (CMV) in eyes with CMV corneal endotheliitis. Methods We reviewed the medical charts of four cases of corneal endotheliitis that were CMV-positive. We have classified types of clinical phenomenon into four types: coin-shaped KPs, sectoral corneal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The authors recommended that combined topical steroid with antiviral therapy might be indicated in CMV endotheliitis with sectoral corneal edema with and without Khodadoust line-like KPs and mutton-fat KPs. Where antiviral treatment alone could suffice in eyes with coin-shaped KPs [ 70 ], topical steroids should be used judiciously in the treatment and maintenance of CMV endotheliitis and the IOP must be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommended that combined topical steroid with antiviral therapy might be indicated in CMV endotheliitis with sectoral corneal edema with and without Khodadoust line-like KPs and mutton-fat KPs. Where antiviral treatment alone could suffice in eyes with coin-shaped KPs [ 70 ], topical steroids should be used judiciously in the treatment and maintenance of CMV endotheliitis and the IOP must be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…We classified KPs into three types mostly observed in PSS under a slit lamp [20,21]. We found different KP patterns changed differently during PSS prognosis, and disappearance of specific KPs was correlated with the treatment period.…”
Section: Relationship Between Kp Morphology CMV Infection and Pss Prognosismentioning
confidence: 93%
“…Resulted from immune reaction [20], high percent of mutton-fat KP presence indicates severe fresh attack. Pigmented KP is more a sign of historical attack, which is harder to eliminate completely.…”
Section: Relationship Between Kp Morphology CMV Infection and Pss Prognosismentioning
confidence: 99%
“…Moreover, a significant difference in graft ECD between the CMV+ and virus-groups appeared earlier in the PKP subgroup than in the DSAEK subgroup (6mo after PKP vs 12mo after DSAEK), suggesting that CMV replication had a shorter cycle in eyes that underwent PKP, which may be related to a stronger immunosuppressive effect of PKP on the anterior segment [20] . Previous studies found that anterior-segment CMV infections could occur after PKP [10,21] , DSAEK [22][23] , and Descemet's membrane endothelial keratoplasty (DMEK) [18] , but were most common following the PKP procedure. Yoshimura et al [21] first reported a case of CMV positivity after multiple PKP procedures.…”
Section: Graft Endothelial Cell Density and Endothelial Cellmentioning
confidence: 99%
“…Previous studies found that anterior-segment CMV infections could occur after PKP [10,21] , DSAEK [22][23] , and Descemet's membrane endothelial keratoplasty (DMEK) [18] , but were most common following the PKP procedure. Yoshimura et al [21] first reported a case of CMV positivity after multiple PKP procedures. Chee et al [24] reviewed patients who underwent PKP and developed postoperative CMV positivity that manifested as pigmented keratoplasty, corneal neovascularization, and Descemet's folds.…”
Section: Graft Endothelial Cell Density and Endothelial Cellmentioning
confidence: 99%